1992
DOI: 10.1093/carcin/13.11.2191
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the frequency of DNA strand breakage and cross-linking and of sister chromatid exchange frequency in the lymphocytes of patients with multiple myeloma undergoing cytostatic therapy with melphalan and prednisone

Abstract: An investigation was made of 17 patients with multiple myeloma using the method of alkaline filter elution for the detection of DNA damage and the determination of sister chromatid exchange (SCE) frequency in peripheral lymphocytes during a course of chemotherapy with melphalan and prednisone. We were able to detect elevated SCE frequencies in pretreated patients that approximately doubled during the therapeutic cycle. An appreciable level of DNA cross-linking was detected by alkaline filter elution; DNA cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The CFSE-stained NCH421K cells were thus seeded in their dissociated state with 50 nM and 40 nM NHC-Ir(III) (approximately 1/40 of the spheroid IC50) and left for four days. The known cytostatic nitrogen mustard, melphalan [46] was used as a positive control. As a measure of the population's average number of cell divisions, a proliferation score was calculated using the Log2(MFI) of CFSE (as a two-fold difference in fluorescence represents a difference of one cell division), as described by Ahlen et al, (2009) [47].…”
Section: Nhc-ir(iii) Impedes Gsc Proliferationmentioning
confidence: 99%
“…The CFSE-stained NCH421K cells were thus seeded in their dissociated state with 50 nM and 40 nM NHC-Ir(III) (approximately 1/40 of the spheroid IC50) and left for four days. The known cytostatic nitrogen mustard, melphalan [46] was used as a positive control. As a measure of the population's average number of cell divisions, a proliferation score was calculated using the Log2(MFI) of CFSE (as a two-fold difference in fluorescence represents a difference of one cell division), as described by Ahlen et al, (2009) [47].…”
Section: Nhc-ir(iii) Impedes Gsc Proliferationmentioning
confidence: 99%
“…It has been postulated that a decrease in immune cell number could explain the negative SCE effects as fuel exposure increases (Lemasters et al, 1997). The majority of studies on gasoline and oil refineries have shown benzene and toluene exposed workers to have a non significant increase in SCE frequency as a consequence of low continuous exposure (Popp et al 1992, Carere et al, 1995a,b 1998, Major et al 1994. However, soldiers serving in Kuwait while oil fires burned found to have highly significant increases in mean SCEs (McDiarmid et al, 1995).…”
Section: Sister Chromatid Exchange Investigationmentioning
confidence: 99%
“…Η συχνότητα των SCE αυξάνεται όταν αυξάνεται η συγκέντρωση του αλκυλιωτικού παράγοντα ή ο χρόνος έκθεσης των κυττάρων στην αλκυλιωτική ουσία. Η αύξηση της συχνότητας των SCE συνοδεύεται και από μια μείωση του ρυθμού πολλαπλασιασμού των κυττάρων (Littlefield LG 1982, Raposa Τ 1982, Morimoto Κ 1984, Popp W et al 1992. Η καθυστέρηση του κυτταρικού κύκλου που προκαλούν οι αλκυλιωτικοί παράγοντες, μπορεί να χρησιμεύσει ως ένας ευαίσθητος δείκτης κυτταροτοξικότητας (Krishnaswamy G και Dewey WC 1993).…”
Section: ογ κυτταρογενετικες βλαβες που προκαλουν λιαφοροι φυσικοι και χημικοι παραγοντεςunclassified